Comparison of Four Polymerase Chain Reaction Methods for the Rapid Detection of Human Fecal Pollution in Marine and Inland Waters - Dave S. Bachoon; Cortney M. Miller; Christen P. Green; Ernesto Otero (International Journal of Microbiology)
We compared the effectiveness of three PCR protocols for the detection of Bifidobacterium adolescentis and one PCR protocol for detecting Bacteroidales as indicators of human fecal pollution in environmental samples. Quantitative PCR indicated that a higher concentration of B. adolescentis DNA was recovered from sewage samples on the 0.2 μm filters compared to the 0.45 μm filters, and there was no evidence of qPCR inhibitors in the DNA extracts. With the Matsuki method (1999), B. adolescentis was detected only in undiluted sewage samples. The King method (2007) performed well and detected B. adolescentis in all of the sewage dilutions (from undiluted to 10−4). In contrast, the Bonjoch approach (2004) was effective at detecting B. adolescentis at lower dilutions (10−3) of sewage samples and it gave false positive results with some (3/8) pig fecal samples. Human-specific Bacteroidales (HuBacs) were detected in the lower diluents of sewage samples but was positive in pig (6/8) and cattle fecal samples. PCR detection of B. adolescentis in marine samples from Puerto Rico and freshwater samples from Georgia indicated that the PCR method of King et al. (2007) and the modified Layton method for HuBac were in agreement in detecting human fecal pollution in most sites.